2021
DOI: 10.3390/pr9091511
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Drying Characteristics and Drying Quality Analysis of Corn in China

Abstract: To identify the microwave drying characteristics of corn, microwave drying tests were conducted on corn. By taking the moisture content, drying rate, and drying temperature as indices, this research revealed the effects of different microwave powers and loads on the microwave drying characteristics of corn. Moreover, energy consumption and quality of dried corn were analysed under different drying conditions. The results demonstrate that microwave drying has significant energy-saving effects. The energy consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
(41 reference statements)
3
14
0
Order By: Relevance
“…According to Figure4a, the maximum moisture ratio was revealed during the drying of ZD88 at 35 C, followed by 45 and 55 C. While drying RP909, a comparable pattern was observed in Figure4bindicating the moisture removal rate was faster at higher drying air temperatures than at lower ones. This finding was consistent with(Liu et al, 2021;Nayi et al, 2023), where a high moisture removal rate was observed due to a large temperature difference at the boundary of the product, leading to enhanced heat and mass transfer processes at 55 C. Conversely, a reduced drying rate was associated with low temperatures drying at 35 and 45 C. Moreover, Figure5a,b shows increasing the infrared temperature accelerates the rate of drying, enhancing evaporation, and promoting more significant mass and heat transfer rates. However, when the moisture content is low, reducing the drying temperature helps maintain a consistent evaporation rate throughout the drying process(Li et al, 2021).…”
supporting
confidence: 86%
“…According to Figure4a, the maximum moisture ratio was revealed during the drying of ZD88 at 35 C, followed by 45 and 55 C. While drying RP909, a comparable pattern was observed in Figure4bindicating the moisture removal rate was faster at higher drying air temperatures than at lower ones. This finding was consistent with(Liu et al, 2021;Nayi et al, 2023), where a high moisture removal rate was observed due to a large temperature difference at the boundary of the product, leading to enhanced heat and mass transfer processes at 55 C. Conversely, a reduced drying rate was associated with low temperatures drying at 35 and 45 C. Moreover, Figure5a,b shows increasing the infrared temperature accelerates the rate of drying, enhancing evaporation, and promoting more significant mass and heat transfer rates. However, when the moisture content is low, reducing the drying temperature helps maintain a consistent evaporation rate throughout the drying process(Li et al, 2021).…”
supporting
confidence: 86%
“…1 c). Thus, the conjunctional effect of moisture loss and higher core temperature of the samples resulted in the creation of micro-fissures and subsequent reductions in drying time during IRD, particularly for MW5S [16] . Besides, studies have shown that rapid thawing could impede the structural collapse of samples for minimizing drip loss.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the promising results reported by these studies, some quality degradation linked with excessive structural deformations and resultant leaching loss has been associated with the use of FT pretreatments [6] . For example, FT pretreatment was reported to cause damage to the cell wall, leading to increased shrinkage, enzymatic browning, undesirable changes in colour, and losses in phytochemicals during infrared-hot air drying of lotus and microwave drying of Platycodon grandiflorum [16] , [36] . Nevertheless, improved thawing approaches targeting reducing the thawing time for preserving cell structures and components can reduce the negative effects of FT pretreatments on food quality during drying [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The lemon slices were placed on a tray in an experimental MVD chamber (JDH‐3GZ, Guangzhou Yongze Microwave Energy Equipment Co., Ltd., Guangzhou, China) and dried at 1 kW (Liu, H. J., et al., 2021). The weight of the lemon slices was measured and recorded every 2 min until the moisture content was below 12%.…”
Section: Methodsmentioning
confidence: 99%